Implementation of an RFID tag emulator using SDR techniques - Banatao, Julie Ann M.
Radio frequency identification (RFID) is a fast growing technology. It is being widely used today in daily activities and gadgets such as product labels and identification cards. Its rapid growth has brought about a demand for the improvement of the specifications of the RFID system such as read range and reliability. Working head-on with actual RFID tags may prove to be difficult and costly so an alternative way of studying RFID system is needed. An RFID tag emulator can be used to emulate different protocols. It is also helpful since the intermediate processes can be seen and can give insights on how the researchers can improve the system such as its reliability and read range. In this project, an RFID tag emulator based on Software Defined Radio is built. Two RFID protocols are emulated, namelu: UHF EPC Gen 2 or ISO 18000-6C, and ISO 15693. The tag emulator has two stages of implementation, namely simulation in Matlab and Simulink and SDR implementation using the ComBlock® Com-1200? FPGA Development Platform. VHDL codes to be used in the SDR implementation are supposed to be generated from the Simulink models but synthesis of the VHDL codes failed so all models are recreated in Xilinx. The SDR implementation of the protocols is only tested using internally generated bits because of time constraints. It is thus recommended that the Xilinx System Generator be used in conjunction with Simulink when creating models. Succeeding projects can also work on implementing a tag emulator capable of replying to the readers.